Linoleum [videorecording (DVD)] - West, Colin; Gaffigan, Jim; Seehorn, Rhea, 1972-; Nacon, Katelyn, 1999- (Shout! Factory, 2023)
Cameron Edwin, the host of a failing children's science TV show called "Above & Beyond," has always had aspirations of being an astronaut. After a mysterious space-race-era satellite coincidentally falls from space and lands in his backyard, his midlife crisis manifests in a plan to rebuild the machine into his dream rocket. As his relationship with his wife and daughter start to strain, surreal events begin unfolding around him a doppelgänger moving into the house next door, a car falling from the sky, and an unusual teenage boy forging a friendship with him. He slowly starts to piece these events together to ultimately reveal that there's more to his life story than he once thought.